Gender inequality in the labor market: A comparative analysis of wage gaps and job quality in Argentina, Spain, Germany, and Poland - Tuñón, Ianina (2025)
Fil: Tuñón, Ianina. Pontificia Universidad Católica Argentina. Observatorio de la Deuda Social Argentina; Argentina